Entomofauna Of Plants Of The Genus Cerasus (Prunus) And Their Role In The Agroecosystem (Texas Journal of Agriculture and Biological Sciences, 2025)
This article examines the composition, proportion, and ecological interactions of harmful insects and their natural enemies – entomophages – occurring in the cherry (Cerasus spp.) agrobiocenosis of the Fergana Valley during 2020–2025. The study identified 21 species of harmful entomofauna and 48 species of beneficial entomophages. The analysis showed that among pests, the orders Coleoptera (38.1%) and Lepidoptera (19.0%) are dominant, while among entomophages, the greatest proportion belongs to representatives of Diptera and Arachnida (27.1% each). These groups play a crucial role in maintaining the biological balance of the agroecosystem.